Sustainable Ecotourism Design: A Case Study of Bale-Bale Beach, Nongsa - Suwarlan, Stivani Ayuning; Gunawan, I Gusti Ngurah Anom; Rinah; Crisnawati, Seprina; Aprilia, Muthia; Balqista Ratu Ayunda, Ismi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Bale-Bale Beach in Batam has significant potential as a marine ecotourism destination, but it remains underutilized. Key challenges include poor road infrastructure and low tourist interest in coastal activities, largely due to the dominance of floating restaurants. This limits the use of natural assets like mangrove forests, which could support conservation and sustainable tourism. This study aims to develop a sustainable ecotourism concept that integrates natural resources, local culture, and community participation. Its novelty lies in applying a multifunctional zoning approach—conservation, education, and recreation—based on sustainable architectural principles. Using a descriptive qualitative method, the study analyzes regional potential, community needs, and ecological design principles. Data was collected through observation, interviews, and documentation. Findings suggest that Bale-Bale Beach can be developed through an integrated zoning model that connects ecological preservation with educational and recreational activities rooted in local culture. This strategy supports adaptive and participatory coastal tourism development. The proposed concept offers practical insights for stakeholders and local authorities in managing coastal areas sustainably and can serve as a model for similar ecotourism initiatives in Batam and other coastal regions.